Pengaruh Pendidikan Kesehatan Terhadap Tingkat Pengetahuan Remaja Tentang Sadari Sebagai Deteksi Dini Kanker Payudara Pada Remaja - Egi Seviana Regitasari; Mudy Oktiningrum; Nella Vallen (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Breast cancer is recognized as the most common cancer that occurs in women, and the second most common malignant tumor, after lung cancer in the category of cancer diseases worldwide (Bonsu &; Ncama, 2018). According to data from the Global Cancer Observatory, in 2020, there were 19.2 million new cancer cases worldwide, including 2.2 million women diagnosed with breast cancer. There were approximately 685,000 women dying from breast cancer in 2020, accounting for about 15.5% of all cancer deaths in the world (Aprianti et al, 2022).